2022
DOI: 10.1016/j.ctro.2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term volumetric analysis of vestibular schwannomas following stereotactic radiotherapy: Practical implications for follow-up

Abstract: Highlights Pseudoprogression may be a late phenomenon after radiosurgery. Loss of central contrast enhancement is not predictive of tumor control. No decision of salvage therapy should be made until the 6th year post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…The tumor volume can thus decrease significantly initially after treatment in patients with failed medium-to long-term tumor control. Other authors have reported similar observations [12,17,22].…”
Section: Tumor Volume Changes In Patients With Failed Radiosurgery Fo...supporting
confidence: 75%
See 3 more Smart Citations
“…The tumor volume can thus decrease significantly initially after treatment in patients with failed medium-to long-term tumor control. Other authors have reported similar observations [12,17,22].…”
Section: Tumor Volume Changes In Patients With Failed Radiosurgery Fo...supporting
confidence: 75%
“…Modifications of MR imaging after radiosurgery for VS have been studied in some series [17][18][19][20]. Transient tumor volume increase and loss of contrast enhancement are well-known phenomena [18,19,[21][22][23][24][25]. However, the presence of these changes in follow-up MRI of patients with failed therapy has not been well analyzed.…”
Section: Imaging After Radiosurgery For Vsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor progression or recurrence was defined as a more than 10% increase in the tumor volume compared with pretreatment volume. Tumor pseudoprogression, or an early transient increase in the tumor volume after SRS, was not separately evaluated since it cannot be differentiated from true tumor progression in the first five years of follow-up (9,10). Tumor control was defined as the arrest of tumor growth without progression or a decrease in the tumor volume.…”
Section: Treatment Modality and Outcome Assessmentmentioning
confidence: 99%